2019
DOI: 10.1108/bfj-08-2018-0504
|View full text |Cite
|
Sign up to set email alerts
|

Predicting food choice: a meta-analysis based on the theory of planned behavior

Abstract: Purpose The theory of planned behavior (TPB) emerged as one of the main theoretical bases for understanding consumer intentions and behaviors, with robust results covering different topics. In the context of food, the use of theory has motivated the replication and extension of the model under different circumstances. The paper aims to discuss these issues. Design/methodology/approach The aims of this meta-analysis were to synthesize the literature on TPB in the food choice context and analyze the moderator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 49 publications
(53 reference statements)
0
43
0
Order By: Relevance
“…A significant amount of work has demonstrated that attitudes are often strongly related to consumer behavior [ 16 , 17 , 34 , 35 ]. However, little research has probed how attitudes toward GMOs relate to food choices, and how labels indicating either the presence or absence of GMOs differentially impact consumers’ product evaluations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant amount of work has demonstrated that attitudes are often strongly related to consumer behavior [ 16 , 17 , 34 , 35 ]. However, little research has probed how attitudes toward GMOs relate to food choices, and how labels indicating either the presence or absence of GMOs differentially impact consumers’ product evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that attitude can successfully predict subsequent behavior [ 13 , 14 , 15 , 16 , 17 ]. When applied to the current research, this line of work implies that a negative attitude towards GM food products should translate into the behavior of avoiding such products.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have applied this theoretical TPB model to explore consumers' willingness to participate in certain pro-environmental behaviors (e.g., Bamberg, Ajzen, & Schmidt, 2003;Bamberg & Schmidt, 2001;Chen, 2016;Lam, 1999;Terry, Hogg, & White, 1999) and purchase behavior of environmentally sustainable products (Kumar, Manrai, & Manrai, 2017;Lee, Jin, & Shin, 2018). In addition, a meta-analysis conducted by Nardi, Jardim, Ladeira, and Santini (2019) had verified that the application of the TPB model is robust to predict food choice.…”
Section: Introductionmentioning
confidence: 99%
“…Han and Hansen analyzed 16 empirical studies regarding TPB and sustainable food consumption, and their findings show that TPB has adequate power to explain the intention of sustainable food consumption. In particular, attitude (r = 0.62) and subjective norm (r = 0.55) show strong effects on the intention to consume [29]. McDermott and other authors analyzed the variables of TPB associated with discrete food choices in 42 studies, and their results indicated that attitude has the most active association with intention (r = 0.54) followed by perceived behavioral control (r = 0.42) and finally by subjective norm (r = 0.37) [30].…”
Section: Theory Of Planned Behavior For Understanding the Specialty Cmentioning
confidence: 99%